2021
DOI: 10.1177/10422587211046548
|View full text |Cite
|
Sign up to set email alerts
|

Self-Efficacy in Disrupted Environments: COVID-19 as a Natural Experiment

Abstract: In two studies, we investigate whether the link between entrepreneurial self-efficacy and entrepreneurial intentions depends on outcome expectations. In Study 1, we exploit the COVID-19-induced lockdown as a natural experiment in a two-wave student sample. We compare the efficacy–intention link in survey responses submitted right before and right after the lockdown. In Study 2, we conceptually replicate and extend the findings via an online vignette experiment. Together, these studies show that a disruption of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 108 publications
1
12
0
Order By: Relevance
“…We found that the link between EA and EI has become weaker during the pandemic. Along with previous studies [17,66], such as those on entrepreneurial self-efficacy and EI [67], the results give us a deeper understanding of the crisis' influence on entrepreneurship, especially with regard to college students' EI.…”
Section: Research Values and Contributionssupporting
confidence: 61%
“…We found that the link between EA and EI has become weaker during the pandemic. Along with previous studies [17,66], such as those on entrepreneurial self-efficacy and EI [67], the results give us a deeper understanding of the crisis' influence on entrepreneurship, especially with regard to college students' EI.…”
Section: Research Values and Contributionssupporting
confidence: 61%
“…The scales are arranged in the following order: the measure of entrepreneurial intention, the measure of entrepreneurial attitude, the measure of achievement motivation, and the measure of materialism. Moreover, similar to the previous studies (e.g., Bergenholtz et al, 2021 ; Tufa, 2021 ), we adopted the original number of scale points for each measure, i.e., entrepreneurial intention and entrepreneurial attitude were measured on a 7-point Likert scale, and materialism and achievement motivation were measured on a 5-point Likert scale. Using different numbers of scale points in one survey is helpful to reduce common method bias (Jordan and Troth, 2020 ).…”
Section: Methodsmentioning
confidence: 99%
“…Conversely, other scholars argued that, in disrupted times like the COVID-19 pandemic, risk and uncertainty feelings become the cornerstone of university students' SE, decreasing their entrepreneurial intention. Paradoxically, some academics stated that, in disturbing periods like the COVID-19 crisis, risk and uncertainty perceptions loweruniversity students' SE, limiting their entrepreneurial intentions (Bergenholtz et al, 2021;Loan et al, 2021). Notably, related studies have confirmed that SE is the mechanism by which prior experience with social problems leads to SEI (Hockerts, 2018;Ip et al, 2018;Sousa-Filho et al, 2020).…”
Section: Ess and Sei: The Mediating Role Of Sei Antecedentsmentioning
confidence: 99%